ANALISIS KADAR VITAMIN C PADA MINUMAN KEMASAN DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Eky Desi Wulandari (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
This study aims to analyze the content of vitamin C in packaged beverages using the UV-Vis spectrophotometry method. Three different packaged beverage samples were tested, and the results showed variations in vitamin C content. The UV-Vis spectrophotometry method proved effective in analyzing the content of vitamin C in packaged beverages. However, these results can be influenced by various factors, such as the type of fruit used in the drink, processing, and storage. This research provides important insights into the content of vitamin C in packaged beverages, which can be used by producers and consumers to make better decisions about beverage products.